Frequency response modeling and online parameter adjustment of inverter-based source for off-grid renewable energy systems - Tang, Yujia; Tu, Liang; Liu, Yuyan; Yu, Jiawei; Ma, Kaixin (Frontiers in Energy Research, 2025)
Off-grid pure renewable energy systems increasingly rely on inverter-based sources, making their frequency response characteristics crucial for frequency stability analysis. To address the limited interpretability and poor online applicability of existing high-order models, this paper develops a low-order and physically interpretable frequency response model for inverter-based sources. A reduced-order model on the power–frequency time scale is derived to reveal the frequency response mechanism, analytical expressions for key dynamic indicators are obtained, and a Levenberg–Marquardt–based parameter identification method is proposed. An online updating mechanism and parameter adjustment strategy are further designed to handle operating-point variations and low-damping, low-inertia conditions. Simulation results validate the accuracy and robustness of the proposed model, as well as the effectiveness of the identification and updating strategies in practical application scenarios.